Surgery for thumb (trapeziometacarpal joint) osteoarthritis - Wajon, Anne (Cochrane Database Syst Rev, 2015)
BACKGROUND: Surgery is used to treat persistent pain and dysfunction at the base of the thumb when conservative management, such as splinting, or medical management, such as oral analgesics, is no longer adequate in reducing disability and pain. This is an update of a Cochrane Review first published in 2005. OBJECTIVES: To assess the effects of different surgical techniques for trapeziometacarpal (thumb) osteoarthritis. SEARCH METHODS: We searched the following sources up to 08 August 2013: CENTRAL (The Cochrane Library 2013, Issue 8), MEDLINE (1950 to August 2013), EMBASE (1974 to August 2013), CINAHL (1982 to August 2013), Clinicaltrials.gov (to August 2013) and World Health Organization (WHO) Clinical Trials Portal (to August 2013). SELECTION CRITERIA: Randomised controlled trials (RCTs) or quasi‐RCTs where the intervention was surgery for people with thumb osteoarthritis. Outcomes were pain, physical function, quality of life, patient global assessment, adverse events, treatment failure or trapeziometacarpal joint imaging. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by the Cochrane Collaboration. Two review authors independently screened and included studies according to the inclusion criteria, assessed the risk of bias and extracted data, including adverse events. MAIN RESULTS: We included 11 studies with 670 participants. Seven surgical procedures were identified (trapeziectomy with ligament reconstruction and tendon interposition (LRTI), trapeziectomy, trapeziectomy with ligament reconstruction, trapeziectomy with interpositional arthroplasty (IA), Artelon joint resurfacing, arthrodesis and Swanson joint replacement). We did not find any studies that compared surgery with sham surgery or surgery with non‐surgical interventions. Most included studies had an unclear risk of most biases which raises doubt about the results. No procedure demonstrated any superiority over another in terms of pain, physical function, quality of life, patient global assessment, adverse events, treatment failure (re‐operation) or trapeziometacarpal joint imaging. One study demonstrated a difference in adverse events (mild‐moderate swelling) between Artelon joint replacement and trapeziectomy with tendon interposition. However, the quality of evidence was very low due to a high risk of bias and imprecision of results. Low quality evidence suggests trapeziectomy with LRTI may not provide additional benefits or result in more adverse events over trapeziectomy alone. Mean pain (three studies, 162 participants) was 26 mm on a 0 to 100 mm VAS (0 is no pain) for trapeziectomy alone, trapeziectomy with LRTI reduced pain by a mean of 2.8 mm (95% confidence interval (CI) ‐9.8 to 4.2) or an absolute reduction of 3% (‐10% to 4%). Mean physical function (three studies, 211 participants) was 31.1 points on a 0 to 100 point scale (0 is best physical function, or no disability) with trapeziectomy alone, trapeziectomy with LRTI resulted in sightly lower function scores (standardised mean difference 0.1, 95% CI ‐0.30 to 0.32), an equivalent to a worsening of 0.2 points (95% CI ‐5.8 to 6.1) on a 0 to 100 point scale (absolute decrease in function 0.03% (‐0.83% to 0.88%)). Low quality evidence from four studies (328 participants) indicates that the mean number of adverse events was 10 per 100 participants for trapeziectomy alone, and 19 events per 100 participants for trapeziectomy with LRTI (RR 1.89, 95% CI 0.96 to 3.73) or an absolute risk increase of 9% (95% CI 0% to 28%). Low quality evidence from one study (42 participants) indicates that the mean scapho‐metacarpal distance was 2.3 mm for the trapeziectomy alone group, trapeziectomy with LRTI resulted in a mean of 0.1 mm less distance (95% CI ‐0.81 to 0.61). None of the included trials reported global assessment, quality of life, and revision or re‐operation rates. Low‐quality evidence from two small studies (51 participants) indicated that trapeziectomy with LRTI may not improve function or slow joint degeneration, or produce additional adverse events over trapeziectomy and ligament reconstruction. We are uncertain of the benefits or harms of other surgical techniques due to the mostly low quality evidence from single studies and the low reporting rates of key outcomes. There was insufficient evidence to assess if trapeziectomy with LRTI had additional benefit over arthrodesis or trapeziectomy with IA. There was also insufficient evidence to assess if trapeziectomy with IA had any additional benefit over the Artelon joint implant, the Swanson joint replacement or trapeziectomy alone. AUTHORS' CONCLUSIONS: We did not identify any studies that compared surgery to sham surgery or to non‐operative treatments. We were unable to demonstrate that any technique confers a benefit over another technique in terms of pain and physical function. Furthermore, the included studies were not of high enough quality to provide conclusive evidence that the compared techniques provided equivalent outcomes.